Brain Metastases From Differentiated Thyroid Carcinoma: A Retrospective Study of 22 Patients - Wu, Tong; Jiao, Zan; Li, Yixuan; Peng, Jin; Yao, Fan; Chen, Weichao; Yang, Ankui (Frontiers in Endocrinology, 2021)
Background:Brain metastasis from differentiated thyroid cancer shows the same trend with the increase of the incidence of thyroid cancer in recent years. However, the characters and treatments in brain metastases are unclear.The aim of this study was to understand this disease by analyzing patients with brain metastases from differentiated thyroid cancer(DTC). Methods:Between 2000 and 2020, the database of the Sun Yat-sen University Cancer Center was searched for differented thyroid cancer patients.We found 22 patients with brain metastases.The characteristics of the patients,histological features,treatments and time of death were reviewed.The overall survival rate (OS) was calculated by Kaplan Meier method.The survival curves of different subgroups were compared according to baseline characteristics and treatment received. Results:A total of 22 (1.09%) out of 2013 DTC patients in the Sun Yat-sen University Cancer Center database were identified as having brain metastases.The overall median survival time was 17.5 months (range from 1-60 months)after diagnosis of brain metastasis.The performance statue(PS),tumor site,neurosurgery have impact on the survival by Kaplan-Meier analysis.Prognosis of skull metastasis seems better than the intracranial ones.Neurosurgery is the only factor of all kinds of treatments that has an impact on the patients' OS. Conclusions:Brain metastasis from differented thyroid cancer has a bad prognosis.But it can be improved by comprehensive treatments.PS of the patients can greatly affect the survival. Skull metastases have a better prognosis compared with intracranial ones.Radioiodine therapy(RAIT)seems to effectively improve the prognosis of the patients with skull metastases from DTC.